Effects of Balloon Dilation for Idiopathic Laryngotracheal Stenosis on Voice Production. (January 2016) - Hoffman, Matthew R.; Brand, William T.; Dailey, Seth H.
Objective: To evaluate the effects of balloon dilation for idiopathic laryngotracheal stenosis on voice production. Methods: Retrospective review of 10 female patients with idiopathic laryngotracheal stenosis undergoing balloon dilation. Voice outcomes were evaluated by comparing pre- and posttreatment patient-reported, perceptual, aerodynamic, and acoustic parameters. Complete data sets were not available for all subjects; sample size for each parameter is reported with the corresponding result. Results: Total Voice Handicap Index (VHI) decreased significantly (22.9 ± 13.5 to 6.8 ± 6.5; n = 8; p = .015), as did glottal function index (7.2 ± 4.9 to 1.5 ± 2.0; n = 6; p = .022). No changes were observed in the GRBAS (grade, roughness, breathiness, asthenia, strain) scale. Changes in aerodynamic parameters were not statistically significant. Percent jitter decreased (1.32 ± 1.37 to 0.60 ± 0.29; n = 7; P = .078), and fundamental frequency range was preserved (507 ± 325 to 612 ± 281; n = 7; P = .309). Conclusions: Our sample of patients with idiopathic laryngotracheal stenosis had a mild-moderate dysphonia that improved with balloon dilation. Importantly, adverse effects on voice that can occur with open procedures were not observed. Patient perception of dysphonia improved while fundamental frequency range was maintained and aerodynamic parameters remained within or moved toward the normal range. Larger prospective studies are warranted to further evaluate changes in voice production associated with balloon dilation.